2008
DOI: 10.1111/j.1469-7580.2008.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial performance in the Komodo dragon (Varanus komodoensis) as revealed by high‐resolution 3‐D finite element analysis

Abstract: The Komodo dragon ( Varanus komodoensis ) displays a unique hold and pull-feeding technique. Its delicate 'space-frame' skull morphology differs greatly from that apparent in most living large prey specialists and is suggestive of a high degree of optimization, wherein use of materials is minimized. Here, using high-resolution finite element modelling based on dissection and in vivo bite and pull data, we present results detailing the mechanical performance of the giant lizard's skull. Unlike most modern preda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 46 publications
5
91
0
Order By: Relevance
“…Dromaeosaurs are here found to be low-efficiency biters, but this does not preclude the possibility that they were 'big-game hunters' (Paul 1988, p. 364) because if they did indeed use their sickle claws, then 'the jaws were secondary weapons' (Paul 1988, p. 364). Further, weak-biting Varanus komodoensis (Moreno et al 2008) is capable of inflicting deep wounds through saw-motion biting (Auffenberg 1981), so it is not difficult to imagine dromaeosaurs similarly delivering saw-motion bites if kicks were not enough to kill their prey.…”
Section: Results (A) Biomechanical Profilingmentioning
confidence: 99%
“…Dromaeosaurs are here found to be low-efficiency biters, but this does not preclude the possibility that they were 'big-game hunters' (Paul 1988, p. 364) because if they did indeed use their sickle claws, then 'the jaws were secondary weapons' (Paul 1988, p. 364). Further, weak-biting Varanus komodoensis (Moreno et al 2008) is capable of inflicting deep wounds through saw-motion biting (Auffenberg 1981), so it is not difficult to imagine dromaeosaurs similarly delivering saw-motion bites if kicks were not enough to kill their prey.…”
Section: Results (A) Biomechanical Profilingmentioning
confidence: 99%
“…Finite element analysis (FEA) represents a significant development in the investigation of skull biomechanics, and has been used to assess stress and strain distributions in skulls consequent upon diverse loadings designed to model aspects of food acquisition and processing (e.g. Rayfield et al 2001;Grosse et al 2007;Kupczik et al 2007;McHenry et al 2007;Wroe et al 2007;Curtis et al 2008;Moazen et al 2008;Moreno et al 2008). This technique has also been used to investigate the extent to which skull morphology is optimized to its mechanical functions by iteratively adapting initial simple geometries to stress patterns arising from diverse loading scenarios (Witzel & Preuschoft 1999Preuschoft & Witzel 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1). Three-dimensional finite element (FE) modeling has suggested that the skull and bite force of V. komodoensis are weak (2). However, the relevance of bite force and cranial mechanics to interpretations of feeding behavior cannot be fully evaluated in the absence of comparative data.…”
mentioning
confidence: 99%